Multifarious and Interactive Roles of GRAS Transcription Factors During Arbuscular Mycorrhiza Development - Ho-Plágaro, Tania; García-Garrido, José Manuel (Frontiers in Plant Science, 2022)
Arbuscular mycorrhiza (AM) is a mutualistic symbiotic interaction between plant roots and AM fungi (AMF). This interaction is highly beneficial for plant growth, development and fitness, which has made AM symbiosis the focus of basic and applied research aimed at increasing plant productivity through sustainable agricultural practices. The creation of AM requires host root cells to undergo significant structural and functional modifications. Numerous studies of mycorrhizal plants have shown that extensive transcriptional changes are induced in the host during all stages of colonization. Advances have recently been made in identifying several plant transcription factors (TFs) that play a pivotal role in the transcriptional regulation of AM development, particularly those belonging to the GRAS TF family. There is now sufficient experimental evidence to suggest that GRAS TFs are capable to establish intra and interspecific interactions, forming a transcriptional regulatory complex that controls essential processes in the AM symbiosis. In this minireview, we discuss the integrative role of GRAS TFs in the regulation of the complex genetic re-programming determining AM symbiotic interactions. Particularly, research being done shows the relevance of GRAS TFs in the morphological and developmental changes required for the formation and turnover of arbuscules, the fungal structures where the bidirectional nutrient translocation occurs.